A Research Proposal of Payroll Management System and Attendance Monitoring for Rf Payumo Constructions and Supply in Norzagaray Bulacan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Software designed to automate the payroll process is called a payroll system. These systemsare used to keep track of employee working hours, calculate salaries, calculate taxes anddeductions, print payslips, and more. They can be integrated with leave and attendancetracking systems and the employee self-service portal.The developed system can monitor or oversee everything having to do with the most commonway of paying workers and recording business charges. They are put in place to calculatewages, withhold taxes, and other deductions, print and deliver checks, and pay employmenttaxes to the government. Most of the parts of the payroll management system are currentlyfunctional and ready for implementation, and the other parts remain prototyped and need to befinalized by an IT Specialist. The following discussion based on the developed payrollmanagement system states that the researchers solve the following problems: MonitoringAttendance, Inaccurate Information, Disputes on Salary, and Pay slips that we provide to eachemployee.The Payroll System for Attendance Monitoring is a system where the daily records of eachemployee are recorded. After testing, it was found that the technology used was compatiblewith Structured Query Language (SQL)). It successfully runs the payroll system, including thepersonal information of the employees and the mandatory government contributions.
Keywords: Business